Credit in Peru Among World’s Most Expensive - Mauricio Pachas, Pablo Willins (2017)
The objective of the research is to identify the effects of the cost of money in the Peruvian financial system on the development of companies and the rate of informality in them. Methods of qualitative study, descriptive correlational design; A comparative study was analyzed with the historical information of the Peruvian financial system in relation to that of model countries. In addition to using financial indicators of international acceptance.It was evidenced that high cost of money in the Peruvian financial system, has a negative impact on the development of microenterprise, in turn, they resort to informality as a solution to their demand for capital. The situation of microenterprises facing the demand for money can be solved through strategies of effective support and promotion, thus reducing the current level of informality. Likewise, the positive impact of these strategies would improve the equity level of microenterprises.